A chitinase from Euphorbia characias latex is a novel and powerful plant‐based pesticide against Drosophila suzukii. (26th June 2017) - Martos, S.; Spanò, D.; Agustí, N.; Poschenrieder, C.; Pintus, F.; Moles, L.; Medda, R.
ABSTRACT: Drosophila suzukii attacks on developing soft fruits have recently caused important economic losses in Europe. This study explores the effectiveness of a new control strategy against this insect pest that is based on a plant chitinase extracted from the latex of the Mediterranean spurge, Euphorbia characias . The ability of the purified Euphorbia latex chitinase (ELC) to degrade the chitin exoskeleton of D. suzukii was assessed using confocal laser scanning microscopy. ELC treatment caused reduced larval growth, higher mortality and notable degradation of external insect structures. Therefore, the chitinase may induce a double effect on the D. suzukii larvae, a direct injury on the larval bodies and an action as antifeedant. The effects of the ELC treatment were also tested on leaves of the insect's host plants, Fragaria × ananassa and Rubus idaeus, using physiological parameters (chlorophyll concentration, chlorophyll fluorescence, leaf gas exchange and water potential) and defence gene expression ( FaPGIP, FaChi2_1 and FaChi2_2 ) as stress indicators. ELC at concentrations effective against D. suzukii did not damage the host plants. Only plant defence gene expression was somewhat enhanced during the early hours after ELC application. In conclusion, ELC, a natural product, proved to be an effective tool for use in the development of an environmentally friendly integrated management strategy against D. suzukii, a pest whose control by conventional chemical insecticides is problematic.